Curcumin sensitizes chemotherapeutic drugs via modulation of PKC, telomerase, NF-κκB and HDAC in breast cancer. (October 2011) - Roy, Madhumita; Mukherjee, Sutapa; Sarkar, Ruma; Biswas, Jaydip
Background: Several tumor markers are overexpressed in breast cancer. Chemotherapy in breast cancer fails due to resistance to chemotherapeutic drugs. A phytochemical such as curcumin can be used in a therapeutic modality as it elicits anti-tumor effects.Methods: Action of curcumin on the expression of several tumor markers, such as protein kinase C, telomerase, NF-κκB and histone deacetylase in MCF-7 (ER positive), MDA-MB-231 (ER negative), MCF-12F (control) and also in mice mammary tumors were investigated.Results: Curcumin downregulated the expression of tumor markers both in vitro and in vivo and sensitized tumor cells to the chemotherapeutic drugs cyclophosphamide and paclitaxel.Discussion: Curcumin may be of considerable value in synergistic therapy of cancer such that the drug dose level could be minimized reducing the associated toxicity.